Principles of phonetics - Laver, John. (Cambridge : New York : Cambridge University Press, 2002)
Underlying the apparent diversity shown by the thousands of mutually incomprehensible languages of the world, there is a remarkable, elegant and principled unity in the way that these languages exploit the phonetic resources of speech. It is these principles that Professor Laver sets out to describe in this major new textbook.
Includes bibliographical references (p. 622-684) and index.
Keywords: Phonetics; Phonétique.; Phonetik